Simulation Time and Energy Test for Topology Construction Protocol in Wireless Sensor Networks - Satyam Gupta; Gunjan Gupta (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
Coverage area and energy consumption are very big challenges in the field of Wireless Sensor Networks (WSNs) as it affects the number of sensors, connectivity and network. Since the sensors are operating on battery of limited power, it is a challenging aim to design an energy efficient Topology Control protocol, which can minimize the energy and thereby extend the lifetime of the network. Through this paper an attempt has been made in terms of simulation time and spent energy in construction of topology in the sensor network by comparing Just Tree and K-neigh Tree protocols. The result shows that K-neigh Tree protocol consumes less energy than Just Tree protocol.